Media Video Tutorial terhadap Kemampuan Vokasional Membuat Minuman Es Teh pada Siswa Disabilitas Intelektual Sedang Kelas IX - Abdul Jalil; A Zulkarnain Ali; Sugihartatik Sugihartatik (JOEAI (Journal of Education and Instruction), 2026)
This study aimed to determine the effect of video tutorials on the vocational skills of making iced tea among 11th-grade students with moderate intellectual disabilities at Bondowoso State Special Needs High School (SMLB). This study used a Single Subject Research (SSR) approach through an A-B design involving one student, identified as F, as the subject. The results showed that vocational skills in making iced tea improved after the intervention. This improvement was demonstrated by an upward trend in the data, a positive level change, and a 0% overlap percentage. Based on these findings, video tutorials have been proven to have a positive influence as a means of developing the vocational skills of 9th-grade students with moderate intellectual disabilities at Bondowoso State Special Needs High School.   Keywords: Intellectual Disability, Iced Tea, Vocational Skills, Video Tutorials